Hand and oral hygiene workshop for children in a university extension project: Experience report - Campiolo, Cristiane Priscila; Rutz da Silva, Silvio Luiz; Lopes, Mario Cezar; do Rocio Oliveira, Marilisa; Veber, Ana Paula; Ferreira Silva Júnior, Manoelito (Guará Journal, 2023)
The objective of this study is to report the development of an educational workshop on hand and oral hygiene for children during an extension activity. The educational workshop on hand and oral hygiene was developed for children aged 3 to 12 in the municipality of Teixeira Soares, Paraná, in 2019, during a Rondon Operation at the State University of Ponta Grossa. The workshop was designed and delivered by three dentistry students under the supervision of two professors. To develop the target audience's cognitive (knowledge) skills, a dialogic approach was planned, and a supervised practical session was planned for psychomotor (technical skills). Approximately thirty children participated in the workshop, and the activity was divided into three groups, aiming to make the group more homogeneous by age group. Even using the same teaching resources, the language and approach were readjusted. The activity provided training on oral health information relevant to their age group and motivated them to perform hand and oral hygiene using appropriate techniques. The experience enabled the development of materials with recyclable, interactive, and low-cost resources, with a humanized academic training that is articulated with the community.
Keywords: Education; House infection; Oral health; Child